Assessing the Performance of Factors Affecting the Profitability of the Banking System: Evidence from Kosovo - Durguti, Esat A.; Krasniqi, Enver H.; Krasniqi, Dea (European Journal of Sustainable Development, 2020)
This review done by empirical surveillance observes the significances of a number of the explicit factors of the bank that are matching to bank governance, financial market configuration on one hand, and macroeconomic aspects of the Kosovo bank's performance on another hand. The Management and assessment of Kosovo's bank effectiveness were accomplished through two indicators return on assets (ROA) and return on equity (ROE). To recognize this assessment, the OLS, and Arellano-Bond (GMM) regression method will be applied with the data used from the financial statements of Kosovo banks on a periodical basis over the period 2006-2019. Based on the challenging environments in which the banking system of Kosovo has passed, we have carefully chosen some specific determinants of the banking industry, as well as some of the macroeconomic determinants. The outcomes propose that upcoming studies may contain diverse dynamic models as well as altered dependent and independent features to elucidate the performance of Kosovo banks. Keywords: Bank’s profitability, time series, OLS regression, GMM.